2020
DOI: 10.1016/j.jocn.2020.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p38 MAPK signaling pathway on cognitive function and recovery of neuronal function after hypoxic-ischemic brain injury in newborn rats

Abstract: To explore the effects of p38 MAPK signaling pathway on cognitive function and recovery of neuronal function after hypoxic-ischemic brain injury (HIBI) in newborn rats. Seventy-two healthy SPF grade SD newborn rats were randomly and equally divided into Normal group (healthy rats) and Sham group (rats underwent sham operation), Model group (HIBI model rats), p38 MAPK Inhibitor group (HIBI model rats treated with p38 MAPK inhibitor) and p38 MAPK Activator group (HIBI model rats treated with p38 MAPK activator).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Elevated expressions of inflammatory molecules may combine to have a contributing negative effect on neurons in the postnatal hippocampus. Several studies have shown that p38 MAPK phosphorylation increased in the hippocampus and the brain cortex under hypoxic conditions [ 57 ], and this p38 MAPK activation coincided with neuronal apoptosis and cognitive function deficit in young rats [ 58 ]. Central nervous system proinflammatory cytokine overproduction and release activated by p38 MAPK have been reported to promote neuronal damage [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expressions of inflammatory molecules may combine to have a contributing negative effect on neurons in the postnatal hippocampus. Several studies have shown that p38 MAPK phosphorylation increased in the hippocampus and the brain cortex under hypoxic conditions [ 57 ], and this p38 MAPK activation coincided with neuronal apoptosis and cognitive function deficit in young rats [ 58 ]. Central nervous system proinflammatory cytokine overproduction and release activated by p38 MAPK have been reported to promote neuronal damage [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model rats were randomly assigned to 9 groups using the random number table method including sham group ( N = 12), CIBP group (TCI) ( N = 36), CIBP + PAR-2 inhibitor group (TCI + PI group) ( N = 6), CIBP + normal saline group (TCI + N group) ( N = 6), CIBP + PAR-2 control peptide group (TCI + PJ group) ( N = 6), CIBP + PAR-2 inhibitor + ERK activator group (TCI +PI + EA group) ( N = 6), CIBP + PAR-2 inhibitor + dimethyl sulfoxide (DMSO) group (TCI + PI + N) ( N = 6), CIBP + PAR-2 inhibitor + ERK activator + CREB inhibitor group (TCI + PI + EA + CI) ( N = 6), and CIBP + PAR-2 inhibitor + ERK activator + DMSO group (TCI + PI + EA + N) ( N = 6). The model rats were intrathecally injected with 10 µL PAR-2 inhibitor FSLLRY-NH2 (1 mmol/L, FSLLRY-NH2, CAS No.245329-02-6, MedChemExpress, Monmouth Junction, NJ, USA) [ 15 ], PAR-2 control peptide (LRGISL-NH2, Bachem Inc., Torrance, CA, USA), 10 µL ERK activator Dehydrocorydaline chloride (10 mg/kg, HY-N0674A, MedChemExpress) [ 16 ] and 10 µL CREB inhibitor KG-501 (70,485, Sigma-Aldrich, St. Louis, MO, USA) on the 13th d after the operation. The equivalent volume of normal saline (1 mmol/L) and DMSO were set as the corresponding controls.…”
Section: Cibp Rat Model Establishment and Groupingmentioning
confidence: 99%
“…Thereafter, pro-inflammatory cytokines (TNF-α and IL-1β) promote neuronal apoptosis and necrosis, thus impairing neurological functions and inhibiting neurogenesis, which leads to secondary brain tissue injury ( Ziemka-Nalecz et al, 2017 ). Activation of the p38/MAPK signaling pathway inhibits the learning, memory, and motor function of newborn rats with hypoxic-ischemic brain injury and promotes neuronal apoptosis in the hippocampal tissues ( Zhu et al, 2020 ). A recent study found that FPRs play an important role in HIE.…”
Section: Role Of Formyl Peptide Receptor In Neurological Disease Via Regulation Of Inflammationmentioning
confidence: 99%
“…A recent study found that FPRs play an important role in HIE. Activation of FPR2 with RvD1-attenuated neuroinflammation interacted with the Rac1/NOX2 signaling pathway, causing a decrease in the infarcted region and alleviating neurological deficits after HIE ( Zhu et al, 2020 ). After hypoxic-ischemic injury, excessive glutamate release, free radical production, and an increase in BBB-permeability occur due to energy failure ( Moretti et al, 2015 ).…”
Section: Role Of Formyl Peptide Receptor In Neurological Disease Via Regulation Of Inflammationmentioning
confidence: 99%